Corrosion of grinding media. - Del Rosario, Antonio F. Jr (Philippine Engineering Journal)
An experimental technique in resolving wet grinding media wear into its mechanical and corrosive wear component is presented. The results of the tests indicated that wet grinding media wear is approximately 46 percent mechanical wear and 54 percent corrosive wear.